Exploring the psychosocial characteristics of women with gambling disorder through a qualitative study - Estévez, Ana; Macía, Laura; Ontalvilla, Andrea; Aurrekoetxea, Maite (Frontiers in Psychology, 2023)
Introduction Gambling disorder is a behavioral addiction that has been primarily male, but in the last few years, the age of onset has been equated between the sexes. The profile of female gamblers could be different from that of men. Consequently, this study analyzes the testimonies of women with gambling disorder to determine their specific characteristics (gambling motives, gambling preferences, and associated pathologies). Method The sample comprises 18 women with gambling disorder aged between 30 and 68. Three discussion groups were held, and a “blind” inductive process was carried out to extract categories. The Atlas.Ti 22.0 program was used to recode and analyze the data. Results Results show that women may start gambling due to abuse suffered in childhood, and often family members initiate women into gambling. Likewise, the onset of gambling could be a maladaptive way to manage negative emotions. Also highlighted is the predominance of feelings of social stigmatization, which can be reflected in women’s choice of games where they are not visible. Comorbidity with other disorders such as depression, anxiety, bipolar disorder, personality disorders, and the use of other substances are noteworthy. Discussion The factors explaining why female gamblers do not seek treatment compared to male gamblers are analyzed. More studies on women’s experience with gambling are needed to address the specific characteristics of gambling disorder in women.